Craniofacial Osteosarcomas: Plain Film, CT, and MR Findings in 46 Cases - Lee, Ya-Yen; Van Tassel, Pamela; Nauert, Craig; Raymond, A. Kevin; Edeiken, Jack (American Journal of Neuroradiology, 1988)
Forty-six osteosarcomas of the cranial and facial bones were reviewed radiographically by using the conventional parameters for long bone tumors. There were 32 de novo osteosarcomas (11 maxillary, 13 mandibular, and eight cranial) and 14 postradiation osteosarcomas. All the maxillary tumors originated from the alveolar ridge, and the majority of mandibular lesions began in the body of the mandible. The postradiation osteosarcomas occurred in portions of bones at the borders of the radiation field; the latent period ranged from 4 years, 2 months to 50 years (mean, 14 years). The majority of de novo or postradiation craniofacial osteosarcomas were osteolytic with a long transition zone and no periosteal reaction; the exception was in the mandible, where nearly half the cases were osteoblastic and periosteal reaction was occasionally present. Tumor matrix mineralization occurred in more than 75% of the cases, and osteoid matrix calcification was most frequent, even though most tumors were chondroblastic. Soft-tissue extension of tumor was present in all cases and contained calcifications in more than half. Conventional radiographs are of limited value in evaluating head and neck osteosarcomas because of the superimposed bony structures. CT provides excellent detection of tumor calcification, cortical involvement, and, in most instances, soft-tissue and intramedullary extension. MR is even more effective in demonstrating the intramedullary and extraosseous tumor components on both T1- and T2-weighted images. However, CT and plain films are superior to MR in detecting the matrix calcifications and bone destruction or reaction.